THE SOVEREIGNTY OF JURY VERDICTS AND THE POSSIBILITY OF CRIMINAL REVIEW IN JURY TRIALS (CIPEEX, 2025)
This study examines the relationship between the constitutional sovereignty of jury verdicts (Federal Constitution, art. 5, XXXVIII) and criminal review under the exhaustive hypotheses of Code of Criminal Procedure art. 621. It is a bibliographic study that systematizes Brazilian doctrine and case law to identify admissibility criteria and the limits of review over jury decisions. The aim is to delineate, from the standpoint of legal certainty, the situations in which review may lead to acquittal, reclassification or disqualification, annulment of the trial, or sentence modification without infringing the sovereign will expressed by jurors. The method consisted of a critical analysis of scholarship and precedents, with emphasis on the construction of items I–III of art. 621 and on the requirement of new, reliable, and material evidence. The findings indicate that sovereignty is not absolute and yields in the face of manifest factual or legal error, decisions contrary to the record, or supervening evidence capable of producing a different outcome. The conclusion is that criminal review, when pursued under strict criteria and as an exceptional remedy, functions as a guarantee of substantive justice and a mechanism for correcting miscarriages, thereby reinforcing the credibility of jury trials.
Keywords: jury; criminal review; legal certainty; Evidence